2018
DOI: 10.1186/s13007-018-0309-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of essential oil distribution in the root cross-section of Valeriana officinalis L. s.l. by using histological imaging techniques

Abstract: BackgroundThe essential oil is an important compound of the root and rhizome of medicinally used valerian (Valeriana officinalis L. s.l.), with a stated minimum content in the European pharmacopoeia. The essential oil is located in droplets, of which the position and distribution in the total root cross-section of different valerian varieties, root thicknesses and root horizons are determined in this study using an adapted fluorescence-microscopy and automatic imaging analysis method. The study was initiated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The remaining oil droplets are located in the inner regions (parenchyma), with varying density gradients from the inner to the outer regions depending on genotype, root thickness, and harvesting depth. Further studies are needed to evaluate the relationship between the EO droplet density and EO content [ 326 ]. However, contrary to previous assumption [ 325 ], no linear relationship between oil drop density and root thickness could be derived [ 326 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining oil droplets are located in the inner regions (parenchyma), with varying density gradients from the inner to the outer regions depending on genotype, root thickness, and harvesting depth. Further studies are needed to evaluate the relationship between the EO droplet density and EO content [ 326 ]. However, contrary to previous assumption [ 325 ], no linear relationship between oil drop density and root thickness could be derived [ 326 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Further studies are needed to evaluate the relationship between the EO droplet density and EO content [ 326 ]. However, contrary to previous assumption [ 325 ], no linear relationship between oil drop density and root thickness could be derived [ 326 ]. Despite the harvest process, sowing time and planting density were also found to significantly affect EO yield and percentage.…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…s.l.) is one of the most popular herbal remedies [8,9]. The entire root system is used for medicinal purposes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to containing a great quantity volatile constituents, the essential oils were usually analysed by capillary GC, GC-MS and other instruments (Gränicher et al, 1995;Bos et al, 1997b;Kovacevic et al, 2002;Sati & Mathela, 2005;Safaralie et al, 2008). Fluorescence-microscopy followed by image analysis of entire root cross-sections V. officinalis, showed that the oil droplets displayed varying density gradients from the inner to the outer regions depending on genotype, root thickness and harvesting depth (Penzkofer et al, 2018). As unique constituent for sedative in the essential oils from underground parts of V. officinalis L. s.l.…”
Section: Introductionmentioning
confidence: 99%